2008
DOI: 10.1177/0165025408089273
|View full text |Cite
|
Sign up to set email alerts
|

Replication and extension of Little et al.'s (2003) forms and functions of aggression measure

Abstract: The goal of the current study was to replicate the confirmatory factor analysis of Little et al.'s (2003) aggression measure in an American sample of 69 children (mean age = 12.93 years; SD = 1.27). Although an exact replication of the original model could not be estimated given the small sample, a modified model representing a conceptual replication provided a good fit to the data. Findings suggest that this child self-reported aggression measure can be used with American samples to distinguish four domains o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
48
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 21 publications
13
48
1
1
Order By: Relevance
“…Different results regarding the correlation between age and aggression forms can be seen in the literature. No significant correlation was determined between age and both aggression forms in many studies for instance Fite et al (2008); Little et al (2003); Scarpa et al (2010). However, giving the study conducted by Fung et al (2009), both reactive and proactive aggression correlates to age.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Different results regarding the correlation between age and aggression forms can be seen in the literature. No significant correlation was determined between age and both aggression forms in many studies for instance Fite et al (2008); Little et al (2003); Scarpa et al (2010). However, giving the study conducted by Fung et al (2009), both reactive and proactive aggression correlates to age.…”
Section: Discussionmentioning
confidence: 95%
“…Li and Fung (2015) opined that there is higher proactive aggression in males and no differentiation in reactive aggression in the study of Chinese adolescents as Andreu et al (2009) found in the study of Spanish adolescents. There are studies such as Salmivalli and Nieminen (2002); Uz- Baş and Yurdabakan (2012) indicating that males have higher reactive and proactive aggression than females, yet some studies are of the opinion that there is no significant differentiation by gender in both aggression forms (Fite et al, 2008;. These differences can be explained by cultural factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, not all aggressive youth experience these problems later in life. Ecodevelopmental models that are based on the interaction of risk and protective factors over time between an individual and his or her environment (Richman & Fraser, 2001;Rutter, 2001) suggest multiple pathways to problem behavior (Fite et al, 2008). As risk accumulates, the likelihood of problem behavior also increases.…”
Section: Forms and Functions Of Aggressive Behaviormentioning
confidence: 99%
“…Because aggression is a multidimensional construct (Fite et al, 2008;, testing separate regression models offers greater distinction between the subtypes of aggression by disentangling the forms and functions, thus enabling us to examine a unique set of correlates for each subtype (Fite et al, 2008). Consistent with ecological systems theory, individual factors were entered first in each model, followed by family factors, and then peer and school factors.…”
Section: Theoretical Model Of Aggression Among Girlsmentioning
confidence: 99%